The Hard Skills Bases in Digital Academic Entrepreneurship in Relation to Digital Transformation - Ana Garcez; Ricardo Silva; Mário Franco (Social Sciences, 2022)
Digital transformation (DT) has changed the means and mechanisms for acquiring knowledge, meaning that higher education institutions (HEI) have changed the form of student-lecturer and teaching-learning interaction. Digital transformation must have a relevant role in building the hard skills (HS) necessary for academic entrepreneurship, where HS are easily taught and measured. This study analyses the basis of HS for digital academic entrepreneurship, answering the following research hypothesis: What are the hard skills—entrepreneurial education—for digital academic entrepreneurship and how are they formed? An extensive, inclusive literature review revealed that, due to the possibility of editing, reprogramming and generating digital technology, the basis of DT can support the development of HS in higher education students. The results show that HS can be developed considering three major pillars: (i) Management Tools, (ii) Digital Process, and (iii) Digital Products. Since HS are easily taught, this study shows how the use of digital technology can transform this scalable teaching process in order to reach the maximum number of students. It is therefore suggested that those in charge of HEIs use the pillars presented here in the framework proposed to guide their institutions’ strategic planning. With these pillars in mind, the aim is to stimulate the development of innovative business proposals developed in the academic environment and promote digital academic entrepreneurship.